(untitled) (Research, Society and Development, 2020)
As it is a prevalent symptom in the report of most patients, today, pain is a mandatory assessment criterion. The inclusion of pain as the 5th vital sign, with appropriate registration and consequent intervention, ensures that all patients have access to effective measures for pain control. Considering the proximity and the time that the nursing team remains with the patients, it is necessary to promote permanent education directed to these professionals so that, in fact, the systematic assessment of pain occurs. The objective is to describe how pain is recorded as the 5th vital sign in the care of hospitalized patients. It is an integrative review with six articles selected from the Lilacs, PubMed and SciELO databases between 2010 and 2020. After reading, analyzing and interpreting the data, the publications showed that the practice of pain records as 5 The vital sign should be more emphasized, aiming to optimize care and positively influence the patient’s health and quality of life. Thus, the research reflects on the need to provide training to nursing professionals for adequate pain management in hospitalized patients.